Dampak Ekspor Dan Populasi Terhadap Produk Domestik Bruto (PDB) Di Indonesia Periode 1980 Hingga 2015 - ferri Kis Kuswantoro (Jurusan Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis, Universitas Lampung, 2018)
The results of the literature indicated that the impact of exports and population were partially important for the improvement of gross domestic product (GDP). Nevertheless, some studies showedthat exports and population partially were effecting insignificant on economic growth. There were few empirical studies particularly in Indonesia examining how did exports and populationimpacton gross domestic product (GDP) both partially and simultaneously. Using secondary data taken from the world bank, period from 1980 to 2015, assisted by eviews 9, the results of this study indicated that the effect of exports and population were positive significant both partially and simultaneously on gross domestic product (GDP) in Indonesia.